2022
DOI: 10.1093/migration/mnac034
|View full text |Cite
|
Sign up to set email alerts
|

Why do immigrants become less happy? Explanations for the decrease in life satisfaction of immigrants in Germany over time

Abstract: We investigate the life satisfaction (LS) trajectories of immigrants in Germany. Using data from the German Socio-Economic Panel from 1984 to 2015, we find that recently arrived immigrants are more satisfied with their lives than comparable German natives. However, their LS decreases more over time than that of their German counterparts; that is, we observe a negative years-since-migration (YSM)–LS association. We propose and test five possible explanations for this observation: (1) differential effects of dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
0
4
0
1
Order By: Relevance
“…This is the main reason why they feel stuck in the country, potentially leading to increased negative feelings in their immigrant lives. Yaman et al (2022) found that deteriorating health conditions can contribute to decreasing levels of happiness. However, for highly educated immigrants, navigating the education-migration pathway has become challenging, and ‘immigrant life’ has become a burden in fulfilling aspirations developed even before migration, as the findings imply.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the main reason why they feel stuck in the country, potentially leading to increased negative feelings in their immigrant lives. Yaman et al (2022) found that deteriorating health conditions can contribute to decreasing levels of happiness. However, for highly educated immigrants, navigating the education-migration pathway has become challenging, and ‘immigrant life’ has become a burden in fulfilling aspirations developed even before migration, as the findings imply.…”
Section: Discussionmentioning
confidence: 99%
“…This might be because immigrants tend to be healthier, inclined to start a new life, and better educated, allowing them to leverage their capabilities in the host society, in contrast to the lack of opportunities available for them in home countries ( Knies et al, 2016 ; Chen et al, 2022 ; Zafar and Ammara, 2023 ). However, the level of initial happiness among immigrants tends to level off over time, and the daily tasks associated with their new lives can become burdensome, leading to decreased life satisfaction ( Yaman et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bulut and Brewster (2021) examine psychological distress in Middle Eastern immigrants in the US relative to both native-born Whites and immigrants from other global regions. Their results suggest that the average level of psychological distress is higher among Middle Eastern immigrants than among both U.S. Yaman et al (2022), using data from the German Socio-Economic Panel from 1984 to 2015, find that recently arrived immigrants in Germany are more satisfied with their lives than comparable German natives and that their life satisfaction decreases more over time than that Germans. This finding seems to suggest a progressive shift in the reference point of immigrants.…”
Section: Related Literaturementioning
confidence: 98%
“…To gauge the sensitivity of our results to potential bias due to attrition we repeated our estimation including as control variable an indicator which equals 1 for the last interview of a respondent in the panel (see for example Yaman et al (2022)). This did not substantially change our results.…”
Section: Model and Estimationmentioning
confidence: 99%